2015
DOI: 10.21273/jashs.140.4.323
|View full text |Cite
|
Sign up to set email alerts
|

Water Deficit Irrigation Impacts on Antioxidant Metabolism Associated with Freezing Tolerance in Creeping Bentgrass

Abstract: Soil water deficit impacts cold acclimation and freezing tolerance in creeping bentgrass (Agrostis stolonifera L.), but the mechanisms underlying have not been well understood. The objectives of this study were to investigate the effects of deficit irrigation before and during cold acclimation on osmoprotectants, antioxidant metabolism, and freezing tolerance in creeping bentgrass. The grass was subjected to three-soil moisture levels: well-watered [100% container capacity (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…2 ). Simultaneously, the cross acclimation of drought and low temperature has been confirmed in creeping bentgrass ( Agrostis stolonifera L.) ( Zhang et al, 2015 ) and alfalfa ( Xu et al, 2020b ), which provides theoretical support for improving cold resistance of alfalfa by water management. To further understand the relationship between water and cold resistance, we conducted a PCA analysis among root system traits and semi-lethal temperature ( Fig.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…2 ). Simultaneously, the cross acclimation of drought and low temperature has been confirmed in creeping bentgrass ( Agrostis stolonifera L.) ( Zhang et al, 2015 ) and alfalfa ( Xu et al, 2020b ), which provides theoretical support for improving cold resistance of alfalfa by water management. To further understand the relationship between water and cold resistance, we conducted a PCA analysis among root system traits and semi-lethal temperature ( Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Starch can be hydrolyzed into soluble sugar to improve the cold tolerance of alfalfa (Sengupta et al, 2015). In phase 2, the Pro and soluble sugar content of D 8 was still higher than that of the other two cultivars, which indicated that cold acclimation would maximize the cold resistance of alfalfa, but also that a longer irrigation interval can accelerate this process (Xu et al, 2020a;Zhang et al, 2015).…”
Section: Root Physiological Indexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Proline content was examined using the 5-sulfosalicylic acid method, as described in a previous report [40]. Soluble sugar content was measured by the anthrone sulphuric acid method [45]. Photochemical efficiency, including Pn, Ci, Cd, and Tr was estimated using the 6400XT system (Li-Cor, Lincoln, USA) according to the instructions provided by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…Water is a crucial factor that affects the success of alfalfa overwintering because changes in soil moisture content have a greater impact on herbaceous plants [4,5]. On the one hand, sufficient water during the growth period promotes root development and storage of substances for energy; on the other hand, lower intracellular water content in winter reduces the freezing point [6], and freezing injury is mainly caused by cell dehydration [7,8]. Water not only affects the cold resistance of alfalfa by changing the root morphology and architecture, but also protects cells from low-temperature damage through physiological and metabolic pathways [9].…”
Section: Introductionmentioning
confidence: 99%